2012
DOI: 10.1159/000339456
|View full text |Cite
|
Sign up to set email alerts
|

Motor Symptoms and Schizophrenia

Abstract: Classical schizophrenia literature reports motor symptoms as characteristic of the disorder. After the introduction of neuroleptic drugs, the existence of genuine motor disorders was challenged. Renewed interest arose as symptoms were found in never-medicated patients. Reports focused on abnormal involuntary movements, parkinsonism, neurological soft signs, catatonia, negative symptoms, or psychomotor slowing. Since these syndromes refer to different concepts, however, the definitions are not congruent and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
233
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 306 publications
(263 citation statements)
references
References 438 publications
(336 reference statements)
13
233
0
9
Order By: Relevance
“…Longitudinal studies have also demonstrated that children who later develop schizophrenia spectrum disorders had displayed late acquisition of milestones and poor coordination during the first few years of life (Erlenmeyer-Kimling et al 2000;Cannon et al 2002;Welham et al 2009;Clarke et al 2011;Moilanen 2011). These results suggest that motor deficits may serve as risk markers for the illness and are consistent with the neuro-developmental model of schizophrenia (Wolff and O'Driscoll 1999;Tigges et al 2000;Walther and Strik 2012).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Longitudinal studies have also demonstrated that children who later develop schizophrenia spectrum disorders had displayed late acquisition of milestones and poor coordination during the first few years of life (Erlenmeyer-Kimling et al 2000;Cannon et al 2002;Welham et al 2009;Clarke et al 2011;Moilanen 2011). These results suggest that motor deficits may serve as risk markers for the illness and are consistent with the neuro-developmental model of schizophrenia (Wolff and O'Driscoll 1999;Tigges et al 2000;Walther and Strik 2012).…”
Section: Introductionsupporting
confidence: 77%
“…Despite the high prevalence of motor deficits in schizophrenia (78-97% prevalence of NSS in first episode medicationnaive patients), investigations with quantitative measurements remained scarce (Walther and Strik 2012). There are some studies that employed kinematic analysis of repetitive hand movements, such as diadochokinesis and finger tapping (that are subtests included in the NSS rating scales), to evaluate motor function in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, disorganized behavior may also be related to symptoms associated with the motor dimension of schizophrenia, such as stereotypies or ambitendency. 4,6 This view is supported by 2 large studies in first episode medication naïve patients as well as admissions with schizophrenia spectrum disorders demonstrating positive correlations of disorganization and catatonia symptoms such as echophenomena, stereotypies, mannerisms, and agitation. 30,31 Likewise, the PANSS disorganization factor of van der Gaag et al 25 was associated with less predictable movement patterns.…”
Section: Pattern Of Motor Activitymentioning
confidence: 90%
“…10 Activity monitoring using actigraphy allows an objective assessment of schizophrenia motor behavior. 6,11 Reduced activity levels were repeatedly reported in patients using actigraphy. [12][13][14][15] However, few studies have aimed at investigating associations of objective motor behavior and psychopathological phenomena.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation